2019
DOI: 10.3390/f10100833
|View full text |Cite
|
Sign up to set email alerts
|

Necromass Carbon Stock in a Secondary Atlantic Forest Fragment in Brazil

Abstract: Necromass has a relevant role to play in the carbon stock of forest ecosystems, especially with the increase of tree mortality due to climate change. Despite this importance, its quantification is often neglected in tropical forests. The objective of this study was to quantify the carbon storage in a secondary Atlantic Forest fragment in Viçosa, Minas Gerais, Brazil. Coarse Woody Debris (CWD), standing dead trees (snags), and litter were quantified in twenty 10 m x 50 m plots randomly positioned throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
1
2
0
1
Order By: Relevance
“…This reduction in density can be explained by the weight loss due to wood-decomposing microorganisms’ action 61 . Previous studies have also found this pattern of data behavior for CWDs density 37 39 , 50 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This reduction in density can be explained by the weight loss due to wood-decomposing microorganisms’ action 61 . Previous studies have also found this pattern of data behavior for CWDs density 37 39 , 50 .…”
Section: Discussionsupporting
confidence: 79%
“…The arithmetic means of the diameters measured at the ends of the residues was calculated to separate the material into diameters classes with an amplitude of 5 cm. The CWDs found into these plots were divided into 4 classes according to their stage of decomposition 48 50 : (i) Materials that have just fallen to the ground with leaves and bark intact; (ii) Materials similar to those of class “i”, but with the bark showing rotting or peeling; (iii) Materials with a high stage of decomposition and showing some resistance to being broken; (iv) Materials that are rotten, friable and without resistance to being broken.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, o conhecimento dos vários métodos disponíveis para a quantifi cação da necromassa é fundamental para tirar conclusões válidas e para desenvolver estratégias para o manejo destes resíduos fl orestais (Clark et al, 2017). Além disso, o conhecimento de iniciativas que contabilizam o estoque de carbono na necromassa em seus relatórios ou pesquisas científi cas podem contribuir para a valorização dos ecossistemas fl orestais como sumidouro de carbono (Villanova et al, 2019). Desta forma, o objetivo deste boletim técnico foi realizar uma revisão de literatura a respeito dos métodos e iniciativas de quantifi cação do estoque de carbono na necromassa, levando em consideração as principais limitações de cada método e o potencial existente frente à incorporação deste parâmetro às métricas de análise dos ecossistemas fl orestais como sumidouro de carbono.…”
Section: Introductionunclassified
“…In the Atlantic Forest, studies on necromass are in their initial stages. Particularly on the thick necromass compartments (CWD and SDT), there are even fewer studies (Sanquetta, Corte, Pinto, & Melo, 2014;Deus, Bonete, Figueiredo, Dias, & Bonete, 2018;Moreira, Gregoire, & Do Couto, 2019;Fonsêca, Meunier, & Silva, 2019;Villanova et al, 2019).…”
mentioning
confidence: 99%